In the uncharted water: Meaning-making capacity and identity negotiation of Chinese lesbian and bisexual women - Hang, Yang; Zhang, Xiaojun (Frontiers in Psychology, 2023)
Chinese lesbian and bisexual women (LBW) often face difficulties and challenges on campus due to their multiple, socially-oppressed identities. These students have to navigate through uncharted environments to make meaning of their identities. In this qualitative study, by considering four environmental systems of student life, including the student club (microsystem), the university (mesosystem), families (exosystem), and society (macrosystem), we aim to explore what identity negotiation Chinese LBW students have in them and what their meaning-making capacity influence that identity negotiation. We find students experience identity security in the microsystem, identity differentiation-inclusion or inclusion in the mesosystem, and identity unpredictability-predictability or predictability in the exosystem and macrosystem. Moreover, they employ foundational, transitional (formulaic to foundational or symphonic), or symphonic meaning-making capacity to influence their identity negotiation. Suggestions are made for the university to create an inclusive climate accommodating students with different identities.